2017
DOI: 10.20319/mijst.2017.32.381401
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Evaluation of Lowering Atherosclerosis Risk Factors in Hypercholesterolemic Rats and the Immunomodulating Action of Ganoderma Lucidum and Chrysanthemum Indicum Linn

Abstract: This research aimed to address cardiovascular disease, specifically atherosclerosis, by using (t= 2.969, sig. 0.013) and IgG (t= 3.865, sig. 0.003) while no significant decrease in IgA (t=1.683, sig 0.130). Comparison of the treatments using ANOVA showed significant differences between treatments in IgA (F(3,8) =8.458 , p = 0.007.) and IgG (F(3,8) =174.115, sig. <0.0001) but not significant in IgM (F(3,8) = 3.998 , p =.148). There was also significant increase in the number of lymphocytes on R. albus (t=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Six studies reported no significant association between G. lucidum consumption and TC levels. [ 30 31 33 37 44 45 ] However, some studies showed significant beneficial effects of G. lucidum on TC levels. [ 34 35 36 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies reported no significant association between G. lucidum consumption and TC levels. [ 30 31 33 37 44 45 ] However, some studies showed significant beneficial effects of G. lucidum on TC levels. [ 34 35 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported that G. lucidum had a non-significant effect on LDL-C along with other lipid profile components. [ 30 31 44 46 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation